Studies on growth, structural and photoluminescense properties of nisi/sic core-shell nanowires by hwcvd / Nur Fatin Farhanah Binti Nazarudin - Nazarudin, Nur Fatin Farhanah (2014)

(untitled)
NiSi/SiC core-shell nanorods and nanowires grown on nickel (Ni) coated glass substrates by hot-wire chemical vapour deposition were studied. The Ni was used as a catalyst to induce the growth of these core-shell nanorods and nanowires. These nanorods and nanowires were growth at different deposition pressures in the range between 1 and 3 mbar. Increase in deposition pressure prefers to the growth of the nanowires at 3 mbar. These nanowires consisted of single crystalline NiSi and amorphous SiC attributed to core and shell of the nanowires respectively. Moreover, an increase in deposition pressure induces a phase transition of the nanowires from crystalline Si phase to amorphous SiC phase. The shell of the nanowires showed presence of 3C-SiC nano-crystallites embedded within an amorphous matrix. Presence of these nano-crystallites embedded within the amorphous SiC matrix exhibits broad PL emission spectra in visible region. The effects of the deposition pressure on the growth and structural properties of these core-shell nanowires are discussed. Keywords: Core-shell nanowires; Nickel silicides; SiC; Metal induced growth; HWCVD